2016
DOI: 10.1002/adma.201604733
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Control via Structural and Chemical Tuning of Transition Metal Perovskite Chalcogenides

Abstract: Transition metal perovskite chalcogenides are a new class of versatile semiconductors with high absorption coefficient and luminescence efficiency. Polycrystalline materials synthesized by an iodine-catalyzed solid-state reaction show distinctive optical colors and tunable bandgaps across the visible range in photoluminescence, with one of the materials' external efficiency approaching the level of single-crystal InP and CdSe.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
248
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(282 citation statements)
references
References 36 publications
18
248
1
2
Order By: Relevance
“…Five broad peaks can be observed between 50-400 cm −1 , which are identified as 1 1 , 4 , 2 6 , 1 4 , and 1 5 modes. The peak positions match with the theoretical predictions [27,29] and published experimental reports [26,27]. Figures 2(a) -2(d) show the SEM images of BaZrS3 thin films sulfurized from 900 C to 1050 C for 4 hours, respectively.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Five broad peaks can be observed between 50-400 cm −1 , which are identified as 1 1 , 4 , 2 6 , 1 4 , and 1 5 modes. The peak positions match with the theoretical predictions [27,29] and published experimental reports [26,27]. Figures 2(a) -2(d) show the SEM images of BaZrS3 thin films sulfurized from 900 C to 1050 C for 4 hours, respectively.…”
Section: Resultssupporting
confidence: 84%
“…For example, several of them were found to be direct bandgap semiconductors combining both a strong light absorption and a good carrier mobility, which is a rare trait for semiconductors and are hence particularly attractive for optoelectronic applications. Subsequent experimental efforts have succeeded in synthesizing several of the prototypical chalcogenide perovskites as well as related phases including BaZrS3, CaZrS3, SrTiS3, SrZrS3 [26], and SrHfS3 [27,28]. In particular, we further confirmed that BaZrS3 possesses a distorted perovskite structure with a ~1.7 eV [27] bandgap and strong light absorption, in good agreement with our theory.…”
Section: Introductionsupporting
confidence: 86%
“…[110] With as mall amount of Zr substituted by Ti (x = 0.1) in BaZr 1Àx Ti x S 3 they have been able to reduce the bandgapt o 1.47 eV (Figure 9c), al evel within the optimal bandgap range for single-junctionP SCs. [110] Interestingly,t he alloy BaZr 1Àx Ti X S 3 perovskites show reasonable smallc arrier-effective masses, ambipolars elf-doping properties, and theoretical PCEs that are even higher than those of the emerging Pb-halide perovskites for the same thickness. However,D FT calculations and experimental synthesis have also shownt hat it may be difficult to synthesize alloy BaZr 1Àx Ti X S 3 perovskites, as they tend to transform into BaZrS 3 and BaTiS 3 phases.…”
Section: Chalcogenide Perovskitesmentioning
confidence: 96%
“…In addition, the alloy BaZr(O x S 1− x ) 3 was synthesized, and a widely tunable bandgap from 1.73 to 2.87 eV with varying S concentration was observed. Two other recent experiments have reported the bandgap of BaZrS 3 to be between 1.83 and 1.85 eV . This small discrepancy requires further experiments to resolve.…”
Section: Nonhalide Perovskitesmentioning
confidence: 84%
“…Recently, Niu et al synthesized BaZrS 3 (BZS) in a perovskite phase and SrZrS 3 (SZS) in both a needle‐like phase (α‐SZS) and distorted perovskite phase (β‐SZS) . PL spectroscopy showed direct bandgaps of 1.53, 2.13, and 1.81 eV for α‐SZS, β‐SZS, and BZS, respectively.…”
Section: Nonhalide Perovskitesmentioning
confidence: 99%